ANALISA TERJADINYA SIX BIG LOSSES PADA MESIN EVAPORATOR DENGAN METODE TPM DI SEKSI REFINERY MSG PT. XXX - Viga, Tama; Pusakaningwati, Ayik (Journal Knowledge Industrial Engineering (JKIE), 2018)
XXX is a bio industry company that produces MSG, lysine, and tryptophane which can not be separated from issues that corresponded with the Effectiveness of the machine caused by six big losses. Hence, some effective and effecient steps are needed to overcome and prevent the issue. This research focused on evaporator machine in refinery MSG section. The purpose of this research were to analyze the six big losses factors in evaporator machines, to find out overall equipment effectiveness (OEE) value of the evaporator machines, and to purpose improvement efforts based on total productive maintenance (TPM) concept. This research used OEE measurement method, pareto diagram, and cause-effeect diagram to examine existing problem to give solution improvement for the problem. The results showed that 2 most effecting factors of low efficiency in evaporator machine were breakdown losses amount 4,7% and reduced speed losses amount 2,5%. While the results of the OEE calculation carried out on the evaporator machine, the highest OEE value occurred in February 2017 at 88.9% and the lowest OEE value occurred in April at 84.5%. This value is within the OEE standard range of 85%, but fixed improvements must be made to the efficiency of the company. Therefore the proposed corrective actions were to focus of the implementation of autonomous maintenance, planned maintenance, and training and education from the 8 pillars of TPM.